Plastic and Reconstructive Surgeons' Knowledge and Comfort of Contralateral Prophylactic Mastectomy: A Survey of the American Society of Plastic Surgeons - Lopez, Christopher D.; Bluebond-Langner, Rachel; Houssock, Carrie A.; Slezak, Sheri S.; Bellavance, Emily (Frontiers in Oncology, 2019)
Background: Despite limited oncologic benefit, contralateral prophylactic mastectomy (CPM) rates have increased in the United States over the past 15 years. CPM is often accompanied by breast reconstruction, thereby requiring an interdisciplinary approach between breast and plastic surgeons. Despite this, little is known about plastic surgeons' (PS) perspectives of CPM. The purpose of this study was to assess PS practice patterns, knowledge of CPM oncologic benefits, and perceptions of the CPM decision-making process. Methods: An electronic survey was sent to 2,642 members of the American Society of Plastic Surgeons (ASPS). Questions assessed demographics, practice patterns, knowledge of CPM oncologic benefits, and perceptions of the CPM decision-making process. Results: ASPS response rate was 12.5% (n = 329). Most responders worked in private practice (69%), were male (81%) and had been in practice for ≥15 years (60%). The median number of CPM reconstructions performed per month was 2–4. Fifty-five percent of PS reported routine attendance at a breast multidisciplinary conference. Responders reported CPM discussion was most likely to be initiated by the patient (51%) followed by the breast surgeon (38%), and plastic surgeon (7.3%). According to PS, the most common reason patients choose CPM is a perceived increased contralateral cancer risk (86%). Most plastic surgeons (63%) assessed the benefits of CPM as worth the risk of additional surgery and the majority (53%) estimated the complication rate at 2X the risk of unilateral surgery. The majority (61%) of PS estimated risk of contralateral cancer in an average risk patient between <2 and 5% over 10 years, which is consistent with data reported from the current literature. Most plastic surgeons (87%) reported that there was no evidence or limited evidence for breast cancer specific survival benefit with CPM. A minority of PS (18.5%) reported discomfort with a patient's choice for CPM. Of those surgeons reporting discomfort, the most common reasons for their reservations were a concern with the risk/benefit ratio of CPM and with lack of patient understanding of expected outcomes. Common reasons for PS comfort with CPM were a respect for autonomy and non-oncologic benefits of CPM. Discussion: To our knowledge, this is the first survey reporting PS perspectives on CPM. According to PS, CPM dialogue appears to be patient driven and dominated by a perceived increased risk of contralateral cancer. Few PS reported discomfort with CPM. While many PS acknowledge both the limited oncologic benefit of CPM and the increased risk of complications, the majority have the opinion that the benefits of CPM are worth the additional risk. This apparent contradiction may be due to an appreciation of the non-oncologic benefits CPM and a desire to respect patients' choices for treatment.